2020 14th European Conference on Antennas and Propagation (EuCAP) 2020
DOI: 10.23919/eucap48036.2020.9135839
|View full text |Cite
|
Sign up to set email alerts
|

Reducing User Effect on Mobile Antenna Systems With Antenna Cluster Technique

Abstract: This paper studies the use of antenna cluster technique in mobile antenna systems and especially its use in reducing the user effect. The study is conducted with measurements of two different antenna designs using a hand phantom to represent the user holding the device. The results show that antenna designs based on the antenna cluster technique can retain good performance in the presence of a user. Furthermore, the cluster technique can also be used to reduce the user effect by adapting the cluster operation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…An important factor with the antenna clusters and the user effect is the way how the feeding signals and their reconfigurability is used. By properly adapting the feeding signals for the changing environment, it is possible to reduce the user effect [44]. In this work, in addition to the feeding signals, also the tunable capacitor values are reconfigured to the case where the user's hand is holding the device.…”
Section: User Effectmentioning
confidence: 99%
“…An important factor with the antenna clusters and the user effect is the way how the feeding signals and their reconfigurability is used. By properly adapting the feeding signals for the changing environment, it is possible to reduce the user effect [44]. In this work, in addition to the feeding signals, also the tunable capacitor values are reconfigured to the case where the user's hand is holding the device.…”
Section: User Effectmentioning
confidence: 99%
“…In this way, the loss in antenna performance can be compensated for. While we limit our analysis to the free-space case in this work, this possibility has been studied in [32].…”
Section: A Antenna Cluster Techniquementioning
confidence: 99%
“…In [24], it has been shown that the antenna cluster technique can be used to effectively excite characteristic modes of a metal-rimmed device. Due to the distributed feeding and the possibility to adjust the feeding weights differently for use in free space and with the user, the cluster technique can also be used to reduce the user effect even with antenna designs that have not been originally designed to take this into account [25], [26].…”
Section: Introductionmentioning
confidence: 99%